Adjustment Costs in the Theory of Investment of the Firm - Gould, J. P. (Review of Economic Studies, 1968)
Journal Article Adjustment Costs in the Theory of Investment of the Firm Get access J. P. Gould J. P. Gould University of Chicago Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 35, Issue 1, January 1968, Pages 47–55, https://doi.org/10.2307/2974406 Published: 01 January 1968